The relationship between communication apprehension and leadership styles in a job recruitment process - Aprianto, Yudie (International Journal of Communication and Society, 2022)
Nowadays, many organizations seek to accelerate the employees’ communication effectiveness. However, only a few put efforts into reducing communication apprehension and understanding their potential in leadership. This paper seeks to investigate the correlation between communication apprehension and leadership styles, and consequently tries to investigate its impact on individuals’ success in a job recruitment test. A total of 114 participants were gathered in an online survey from a government institution’s recruitment process. The inferential statistic tests (ANOVA) were used to determine differences in leadership styles and their communication apprehension based on respondents’ success in the recruitment process. Results showed that respondents who have high communication apprehension would display task-oriented leadership behaviors and were tended to be more focusing on their role and performance, while the lower communication apprehension indicated more relation-oriented leadership behaviors. Moreover, applicants with a relational leadership style would likely pass a job recruitment test and were more likely to have a successful result in a recruitment process than ones with a task-oriented leadership style. Additionally, this research also gives a glimpse of communication apprehension study in non-western countries. The findings suggest a need for organizations in addressing these issues in order to develop their employees’ communication capacity. Limitations and future research are also discussed in this paper.